The comparison of the efficacy and safety of fractional 1064 nm Nd:YAG picosecond laser and nonablative fractional 1565 nm laser in the treatment of enlarged pores: A prospective split‐face study. Issue 2 (30th January 2023) - Qian, Chunyan; Jiang, Yueqi; Wu, Yuemeng; Yue, Baishuang; Yan, Shuxian; Lu, Zhong
Abstract: Background and Objectives: To compare the efficacy and safety of fractional 1064 nm Nd:YAG picosecond laser and nonablative fractional 1565 nm laser in the treatment of enlarged pores. Study Design/Materials and Methods: Twenty patients received five monthly treatments at months 0, 1, 2, 3, and 4 and were followed up at months 5, 6, and 7. All patients were treated by fractional 1064 nm Nd:YAG picosecond laser (FxPico) on the left face, and nonablative fractional 1565 nm laser (ResurFx) on the right face as a control. Results: For the 19 patients who completed the study, both sides demonstrated significant improvement on pore counts ( p  < 0.01), while there was no significant difference between the two sides 3 months after the final treatment ( p  = 0.092). Excellence rate on the FxPico side (57.9%) was significantly better than the ResurFx side (36.8%) ( p  < 0.05). Sebum secretion and porphyrin value significantly decreased on both sides after five treatments and there was a higher reduction of sebum level on the ResurFx side. There was no difference between the two therapies in terms of overall satisfaction. Pain of treatment for the ResurFx side (average VAS 4.45 ± 1.60) is significantly higher than that for the FxPico side (average visual analog scale [VAS] 1.48 ± 1.36) ( p  < 0.001). Erythema, edema, and petechiae were common adverse effects and were mild to moderate. There was significantly higher incidence of hyperpigmentation for the ResurFx side (52.6%) compared with that for the FxPico side (5.3%) ( p  < 0.001). Conclusion: Fractional 1064 nm Nd:YAG picosecond laser and nonablative fractional 1565 nm laser both are effective, efficient, and safe treatment regimens for enlarged pores, while fractional 1064 nm Nd:YAG picosecond laser has better clinical response with less treatment pain, shorter recovery period and much lower induction of hyperpigmentation.